If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 = 2(3x + 4) Reorder the terms: 44 = 2(4 + 3x) 44 = (4 * 2 + 3x * 2) 44 = (8 + 6x) Solving 44 = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 44 + -6x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 44 + -6x = 8 + 0 44 + -6x = 8 Add '-44' to each side of the equation. 44 + -44 + -6x = 8 + -44 Combine like terms: 44 + -44 = 0 0 + -6x = 8 + -44 -6x = 8 + -44 Combine like terms: 8 + -44 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| 3(3x+9)=9x+27 | | 2x^2+3y-5x=-3 | | 5x+2=23-2x | | 4y(5y-2)=122 | | 4-(5X+7)=6-(X-3) | | 4yx(5y-2)=122 | | -b^4+5b^2+36=0 | | 13*x+72=-23x | | p-24=19/6(18-5) | | 6x+5/x-3+x-6/3x-9 | | 4y=5y-2 | | -7x-5(-4x-11)=-101 | | 10+2x-2x=0 | | 4+2x=36 | | 6x+12=9x+17 | | p-24=19/6(h-5) | | -20+24x+9x^2=0 | | 4x^3-12X^2+20X=0 | | x+5-3x=2x+8-5x | | -4x-3(4x-2)=-86 | | 3(x+1)-4(2x-5)+10x= | | 5X+(X-3)=X-(2X+5) | | f(x)=x^2(6-x) | | 3/4(12x+32)=99 | | -49/7 | | 3+9x=57 | | -175-30x+x^2=0 | | -6x-2=-1x+3 | | (7+2I)-(3-4i)=0 | | 5x+6=48 | | 7n-(3n+8)= | | ((2x^6)/(x^4))((x^2+4x+4)/(4x^7)) |